Investment Education and Literacy - Saputro, Edy Purwo; Kusdiyanto; Setyaningrum, Dewi Probowati (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Investment is one of the keys to supporting accelerated development in poor developing countries, including Indonesia. Therefore, investment cannot be ignored. It is not only related to growth but also employment in various sectors, both formal and informal. Thus, successful investment has a systemic impact to support development. The purpose of this activity is to provide an understanding of investment education and literacy. The main target is the millennial generation, especially from the younger generation with the selection of respondents, namely students of the FEB UMS management program. The activity was carried out on Wednesday, January 11, 2023 at G22 FEB UMS with material, namely structured explanations through power point slides - PPT involving 20 FEB UMS management students. The results show that perceptions about investment are still low so education and literacy are important.